Black Adam : the Justice Society files - Scott, Cavan; Miller, Bryan Q. (DC Comics, 2022)
"One of the world's foremost wielders of magic, Black Adam has been both hero and villain over a life that's spanned thousands of years. But where does that leave him in the fight for justice?"--